From dissertation to book - Germano, William P. 1950- (Chicago guides to writing, editing and publishing, 2013)
Includes a chapter arguing that the future of academic writing is in the hands of young scholars who meet the broader expectations of readers rather than the narrow requirements of academic committees. This title reveals to PhDs the secrets of careful and thoughtful revision.